Effects of Pesticides on Occupationally Exposed Humans - Stylianos M. Piperakis; Konstantina Kontogianni; Michael M. Piperakis; Ricardo Marcos; Smaragdi Tsilimigaki (The Scientific World Journal)
Pesticides are known to contain numerous genotoxic compounds; however, genotoxicity biomonitoring studies of workers occupationally exposed to pesticides have produced variable results. In this study, we employed the Comet assay to examine DNA damage in peripheral blood lymphocytes (PBLs) from 64 greenhouse workers from Almería in south-eastern Spain in comparison to PBLs from 50 men from the same area but not engaged in any agricultural work. The results indicated that there were no differences in the basal levels of DNA damage in the two study groups. In addition, exposure of PBL from the workers and controls to hydrogen peroxide or γ-irradiation led to similar levels of DNA damage; the subsequent repair of the induced DNA damage was also similar for both study populations. Smoking had no impact on any of the responses. The results of this study indicate that the greenhouse workers had no detectable increase in DNA damage or alteration in the cellular response to DNA damage compared to our control population.